2012
DOI: 10.1039/c2jm35199d
|View full text |Cite
|
Sign up to set email alerts
|

Oleamide as a self-assembled cathode buffer layer for polymer solar cells: the role of the terminal group on the function of the surfactant

Abstract: An amphiphilic surfactant oleamide was incorporated into P3HT:PCBM bulk heterojunction polymer solar cells (BHJ-PSCs) as a novel cathode buffer layer (CBL) for the first time by doping in the P3HT:PCBM photoactive layer followed by self-assembly. The power conversion efficiency (PCE) of the annealed P3HT:PCBM/oleamide BHJ-PSC device is enhanced by $28% at the optimum oleamide doping ratio of 2.5%, which is primarily due to the increase of fill factor (FF) by $22%. The surface morphologies of the oleamide-incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 52 publications
6
41
0
Order By: Relevance
“…The stark difference in surface potential suggests that PDIP interlayer could induce a microscopic electric dipole moment with the positive charge end pointing toward Al electrode and the negative charge end pointing toward the active layer (as shown in Fig. 5C) [38,40]. The direction of the dipole moment formed at the interface between active layer and electrode is identical to the built-in potential, which implies that the actual built-in potential across the device is reinforced.…”
Section: Interfacial Dipole Formed Between Active Layer and Metal Elementioning
confidence: 86%
“…The stark difference in surface potential suggests that PDIP interlayer could induce a microscopic electric dipole moment with the positive charge end pointing toward Al electrode and the negative charge end pointing toward the active layer (as shown in Fig. 5C) [38,40]. The direction of the dipole moment formed at the interface between active layer and electrode is identical to the built-in potential, which implies that the actual built-in potential across the device is reinforced.…”
Section: Interfacial Dipole Formed Between Active Layer and Metal Elementioning
confidence: 86%
“…Later, similar to the previous work, oleamide was introduced into the donor/accepter blend to act as an efficient cathode interfacial layer by Zhang et al [45]. The authors found that oleamide molecules tend to self-assemble and migrate to the [53][54][55].…”
Section: Self-organized Cathode Interfacial Layer Materialsmentioning
confidence: 89%
“…PBDTBDD was synthesized according to previous report [14]. All the commercially available materials were used as received without further purification.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Unfortunately, large scale practical application has been inhibited by the poor stability of the devices because the commonly adopted cathode buffer layer (CBL, e.g., calcium (Ca) or barium (Ba)) is prone to oxidative degradation as well as the instable photoactive layer and anode modification layer [9][10][11]. In addition, it is difficult to avoid the interdiffusion of active metal atoms of CBL at the photoactive-layer/metal interface during the thermal evaporation of the CBL, and thus, this leads to an evident performance decrease for PSCs [12] Undoubtedly, the alternative CBL candidates of alkali metal compounds (such as LiF, CsF and Cs 2 CO 3 ) suffer from both of the vacuum involved deposition techniques, which are incompatible with all solution processed PSCs [13,14]. Therefore, considerable efforts have been directed to exploring a stable and solution-processable CBL between an active layer and a cathode since interfacial engineering is a critical factor for the stability improvement of PSCs [15].…”
Section: Introductionmentioning
confidence: 99%